PERAN PEREMPUAN DI IRAN PASCA REVOLUSI 1979 DALAM PERSPEKTIF SHIRIN EBADI - Moh Choirul Anam; Fawaizul Umam; Aminullah . (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
This study aims to comprehensively find out the role of women under the Shah Pahlavi regime. In addition, this study aims to determine the social, political, and economic conditions of Iran after the 1979 revolution. Finally, this study aims to determine the position of women in Shirin Ebadi's view. This research includes library research using a gender approach and a human rights approach. In collecting data, the researcher used the original work of Shirin Ebadi as the primary source, while the secondary data was taken from the works and data related to this research. To process the data, the researcher uses content analysis or content analysis. The results of the analysis explain that Shirin Ebadi has made a big contribution to the struggle of women to get equal rights with men. He was one of the founding initiators of the Center for Defending Human Rights in Iran. Not only that, she became the first female judge in Iran. For handling major criminal cases that dragged important Iranian figures, he was imprisoned by the Iranian government. In 2003, the Norwegian Nobel Committee recognized Shirin Ebadi as the winner of the Nobel Peace Prize for her struggle to defend Iranian women for their rights.